Efecto del Algarrobo (Ceratonia siliqua) para el tratamiento de gingivitis en caninos domésticos (Canis lupus familiaris). - Ibujés Chuquilla, Alexis Daniel (2021)
The purpose of the present investigation was to determine the effect of the Algarrobo tincture (Ceratonia Siliqua) for the treatment of gingivitis in Domestic Canines (Canis lupus familiaris), for which 20 canines from Refugio Peluditos Pujilí were used, who were subjected to the application of Algarrobo tincture in two treatments, prior to a laboratory report. The experimental design research with T Student. The results that were obtained in the project are; for T1 the efficacy of Escherichia coli, beta-hemolytic Streptococcus and Pseudomonas (100%), coagulase negative Staphylococcus (92.2%), Bacillus (75%), Enterobacter cloacae (85%). For T2, an efficacy of Escherichia coli, Bacillus, Enterobacter cloacae (100%), Pseudomonas (94.5%), beta-hemolytic Streptococcus (87.5%), and coagulase negative Staphylococcus (87.5%). With this research, a homeopathic treatment for canine gingivitis was determined, whose beneficiaries are domestic canines with gingivitis, their owners and Veterinary Doctors who can make this protocol a regular use in the clinic